Forming conductive layers at room temperature and inks for forming same using silver nanoparticle processing
By using silver nanowire ink and polysaccharide adhesive to form a conductive film at room temperature, the requirements of high temperature and vacuum in the prior art and the problems of fragility and high cost in ITO are solved, and the formation of a low sheet resistance and high flexibility transparent conductive film is achieved.
Patent Information
- Application Number
- CN202380049308.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-16
- Filing Date
- 2023-06-21
- Publication Date
- 2025-03-18
AI Technical Summary
The prior art has high temperature and vacuum requirements when forming transparent conductive films, and indium tin oxide (ITO) is fragile, expensive, and prone to rupture on flexible substrates.
Silver nanowire ink is used to deposit at room temperature to form a conductive film, which contains about 0.001% to 4% of metal nanowires and about 0.05% to 5% of polysaccharide adhesive, reducing sheet resistance through chemical fusion technology.
A transparent conductive film with low sheet resistance is achieved at room temperature, avoiding the requirements of high temperature and vacuum, and improving the flexibility and durability of the film.
Smart Images

Figure CN119654235A_ABST
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims priority to co-pending U.S. Provisional Patent Application No. 63 / 354,465 filed by Yang et al. on June 22, 2022, entitled “Formation of Fused Silver Nanostructured Networks With Room Temperature Processing and / or on Temperature Sensitive Materials” and U.S. Provisional Patent Application No. 63 / 407,310 filed by Yang et al. on September 16, 2022, entitled “Formation of Electrically Conductive Layers at Room Temperature Using Silver Nanoparticulate Processing and Inks for Forming the Layers,” which are incorporated herein by reference. Technical Field
[0003] The present invention relates to room temperature processing for forming thin conductive coatings, which may be transparent. The present invention also relates to certain silver nanowire inks for forming conductive coatings and conductive coatings on temperature sensitive substrates. Background Art
[0004] Functional films can provide important functions in a range of situations. For example, when static electricity may be undesirable or dangerous, a conductive layer can be important for the dissipation of static electricity. Transparent conductive films can be used as electrodes. High-quality displays can contain one or more transparent conductive layers.
[0005] Transparent conductors can be used in several optoelectronic applications, including, for example, touch screens, liquid crystal displays (LCD), flat panel displays, organic light emitting diodes (OLED), solar cells, and smart windows. Historically, indium tin oxide (ITO) has been the material of choice because of its relatively high transparency at high conductivity. However, ITO has several disadvantages. For example, ITO is a fragile ceramic that requires sputtering for deposition, which is a manufacturing process that requires high temperature and vacuum and is therefore relatively slow and not cost-effective. In addition, ITO is known to crack easily on flexible substrates. Newer portable electronic devices are moving towards thinner and flexible forms. Summary of the invention
[0006] In a first aspect, the present invention relates to a method for forming a conductive layer, the method comprising the steps of depositing a metal nanowire ink onto an inert surface to form a coating and drying the coating at room temperature to form a conductive film. The ink may contain about 0.001 wt % to about 4 wt % of the metal nanowires and about 0.05 wt % to about 5 wt % of the polysaccharide. The conductive film may have a sheet resistance of no more than about 1000 Ohms / sq.
[0007] In another aspect, the present invention relates to an ink for forming a conductive layer, the ink comprising: about 0.001 wt % to about 4 wt % of metal nanowires and about 0.05 wt % to about 5 wt % of a hydroxyalkyl functionalized polymer binder, and about 20 vol % to about 100 vol % of a C1 to C 10 An aqueous solvent of an alcohol, and no more than about 0.001% by weight of a surfactant.
[0008] In another aspect, the present invention relates to a method for forming a conductive coating, the method comprising the steps of applying a silver nanoparticle ink to a substrate surface to form a wet coating, and drying the wet coating at a temperature not exceeding 60° C. to form a dry coating having a sheet resistance of not more than 25 ohms / square. The silver nanoparticle ink may include an aqueous solvent, silver nanoparticles having not more than 85% by weight of silver nanowires having an average diameter of 50 nm or less and an aspect ratio of 10 or more, and a cellulose binder.
[0009] In other aspects, the present invention relates to a silver nanoparticle ink comprising an aqueous solvent, silver nanoparticles having no more than 85% by weight of silver nanowires having an average diameter of less than 50 nm and an aspect ratio of greater than 10, and a cellulose binder, wherein the weight ratio of cellulose to silver nanoparticles is from about 0.05 to about 3. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] Figure 1 is a partial side view of a film having a conductive layer and various additional transparent layers on either side of the conductive layer.
[0011] Figure 2 Schematic diagram showing the relative differences in processing temperature versus time, energy and cost (for contemporary electrode technologies).
[0012] Figure 3 is a graph of the sheet resistance of ink coatings dried with cold air at about 21°C as a function of the level of AgOAc present in the ink used to prepare the coatings.
[0013] Figure 4 Graph showing the sheet resistance of ink coatings dried at about 120°C for 2 minutes as a function of the level of AgOAc present in the ink used to prepare the coatings.
[0014] Figure 5 is a graph of the total transmittance percentage as a function of sheet resistance for an ink coating containing AgF and dried under ambient conditions.
[0015] Figure 6 is a graph of haze percentage as a function of sheet resistance for an ink coating containing AgF and dried under ambient conditions.
[0016] Fig. 7A Photographs showing resistance measurements of ink coatings of the present invention dried under ambient conditions on a medical grade polyurethane substrate.
[0017] Figure 7B FIG. 5 is a photograph showing the resistance measurement of an ink coating of the present invention, which was placed on a medical bandage and dried under ambient conditions.
[0018] Figure 7C Photographs showing electrical resistance measurements of an ink coating of the present invention, which was placed on a leaf and dried under ambient conditions.
[0019] Fig.7D Photographs showing resistance measurements of an ink coating of the present invention, which was placed on a Ziploc® bag and dried under ambient conditions.
[0020] Fig. 7EPhotographs showing resistance measurements of ink coatings of the present invention dried under ambient conditions on a shrink wrapped substrate.
[0021] Figure 7F A photograph showing the resistance measurement of an ink coating of the present invention, the ink coating being located on a Scotch TM On the adhesive layer of the tape substrate, dry under ambient conditions.
[0022] Figure 7G Photographs showing resistance measurements of ink coatings of the present invention formed as circuits on polyethylene terephthalate substrates, dried under ambient conditions.
[0023] Figure 7H Photographs showing resistance measurements of an ink coating of the present invention formed as an electrical circuit on a packaging paperboard substrate, dried under ambient conditions.
[0024] Figure 8 A graph showing the haze percentage as a function of the inverse of sheet resistance for ink coatings prepared with inks containing different fluxes or without flux, dried using cold air only or at room temperature, and then dried at about 120°C for 2 minutes.
[0025] Fig. 9 Shows the display for Figure 8 Bar graph comparing the sheet resistance values obtained for the ink coatings. DETAILED DESCRIPTION
[0026] The ink containing silver nanowires that are easy to process can be formed into a thin layer of conductive material at room temperature. In some embodiments, the conductive coating can be transparent, even highly transparent in the case of extremely low scattering. Good conductivity can be achieved when the nanowires are fused or not, but fusion is generally desirable to form a transparent coating with good mechanical properties, improved stability and better optical properties. The nanowires can be fused into a fused metal nanostructured network, which is an integrated structure with ideal properties. Processing generally involves an ink containing an appropriate amount of polysaccharide binder (such as cellulose ether). In general, the ink is suitable for various coating processes (such as slit coating, dip coating, spray coating or jet deposition, etc.), and can be applied to a series of substrate surfaces. Room temperature processing can advantageously make it possible to process a series of previously unsuitable substrate materials, and can also save energy and cost.
[0027] Silver nanowires have been successfully produced as transparent conductive coatings of high optical quality, which have desirable mechanical properties, such as stretchability and stability against repeated folding and unfolding, while maintaining conductivity. The processing extension described herein can maintain excellent optical quality and extend the required processing of the conductive coating to form a less transparent or non-transparent conductive film. A dispersion or ink of silver nanowires can be deposited on a surface and processed into a conductive coating. Under appropriate process conditions, the resulting conductive coating (optionally transparent) can be ideal for its mechanical properties (such as flexibility, formability, a combination of these features, or other aspects of the conductive coating). In the art, "nanoparticles" are additionally used to specifically refer to roughly spherical nanostructures and to refer to nanostructures of any shape. In order to reduce the burden of the term, "nanoparticles" are used herein to refer to nanostructures of any shape, while "nanoparticles" refer only to roughly spherical nanostructures (i.e., the ratio of the diameters along the three major axes is less than about 2 on average). With regard to transparent coatings, the use of nanowires to form transparent conductive coatings can have important applications in devices with displays and touch sensors. As the metal loading becomes higher, it is found that the resistance decreases while the transmittance of visible light decreases. Even well-purified silver nanowires have a small portion of other silver nanoparticle contaminants, and in the case of less transparent or non-transparent applications, the nanowires can be mixed with other nanoparticles with a slightly larger weight fraction. With the ability to process at room temperature, the formation of a non-transparent conductive layer can be ideally formed on a temperature-sensitive substrate. For optically insensitive coatings, it may be ideal to include additional nanoparticles to improve conductivity or reduce costs (less purification). Therefore, the processing described herein can be practically applied to a wider range of conductive coating applications. Room temperature processing was originally described in U.S. Provisional Patent Application 63 / 354,465, entitled "Formation of Fused Silver Nanostructured Networks WithRoom Temperature Processing and / or on Temperature Sensitive Materials", filed by Yang et al. on June 22, 2022, which is incorporated herein by reference.
[0028] In some embodiments, a metal-based transparent conductive component (e.g., coating) comprises a sparse metal conductive layer. The conductive layer is usually sparse to provide the desired amount of optical transparency through the conductive structure (rather than around the conductive structure), so the metal coverage usually has significant (but microscopic) gaps on the layer of the conductive component. For example, the transparent conductive coating may include metal nanowires deposited along the layer, in which sufficient contact can be provided for electron penetration to provide a suitable conduction path. The one-dimensional morphology of the nanowires helps to form a sparse metal conductive layer. In a particularly interesting embodiment, the transparent conductive coating may include a fused metal nanostructured network, which has been found to exhibit ideal electrical properties, optical properties, and mechanical properties. In a fused structure, unlike a non-fused structure, electrons can be conducted through the network rather than jumping between separated nanowires. Unless otherwise specifically indicated, the conductivity mentioned in this article refers to conductivity. However, the conductive coating described can also act as a transparent heater via Joule heating under an applied voltage. The structure described herein can also be effectively used to form a non-transparent conductive coating processed using a solution coating process at room temperature.
[0029] The application of the applicant's fusion process can be controlled to selectively deposit metal at the junction between metal nanowires, or to form a fused mass of a less conductive structure, regardless of the nanoparticles. In order to form a fused metal nanostructured network, the fusion process can be controlled to deposit a desired amount of silver associated with the junction. The system can be prepared to provide a thermodynamic drive for fusion to occur primarily at the junction between adjacent metal nanowires, which are components formed into a fused metal nanostructured network. After fusion, an integrated structure known as a fused metal nanostructured network is formed, and the original metal nanowires within the conductive structure lose their respective identities. Evidence shows that the fused metal merges the original individual nanowires to reduce or eliminate junction resistance, which would involve the joining of individual nanowires. For commercial products, it is desirable to improve the durability of transparent conductive coatings under a range of real-world conditions. These principles apply to room temperature processing as described herein.
[0030] For transparent coatings, when high-quality silver nanowires are used, it has been found that the fusion process to form the fused metal nanostructured network produces a highly transparent and highly conductive structure with very low haze. Through the use of appropriate stabilizers, the fused metal nanostructured network has been shown to have excellent stability under accelerated wear conditions. The addition of precious metal ions (such as silver) in the overcoat can provide additional levels of stability, as described in Yang et al., entitled "Coatings and Processing of Transparent Conductive Films for Stabilization of Sparse Metal Conductive Layers", which is incorporated herein by reference.
[0031] In the previous research of applicant based on the fusion (thermodynamically driven fusing) driven by thermodynamics, in a relative sense, this processing is carried out at low temperature. However, heat is used to control the drying rate and control the fusion process and accelerate other kinetic processes, reaction rate and diffusion. In the case of the commercial processing of conductive film, roll-to-roll processing has been developed using existing process equipment, so that the required heating with consistent product quality is provided, and appropriate heating is easy to implement. However, heating does consume energy, and does produce constraints to substrate. Especially, many plastic substrates, polymer substrates and biological related substrates show low glass transition temperature and / or low melting temperature, which requires low processing temperature.
[0032] When faced with processing of particularly heat-sensitive substrates, efforts have been made to reduce process temperatures. Surprisingly, a system has been developed that achieves low sheet resistance and rapid results at room temperature processing using a single ink deposition. These results are again consistent with a prepared thermodynamic system that can be directed to achieve the desired results through the application of a little faith and a properly tuned chemical combination (as discovered as described herein). With the achievement of these results, it can be appreciated that the desired processing improvements can also be applied to applications with less demanding optical properties or even non-transparent applications with beneficial effects.
[0033] As shown in the results presented herein, the composition of the silver nanowire ink determines the effectiveness of forming a good conductive layer with or without causing the nanowires to fuse into a fused metal nanostructure network or other fused conductor and at temperatures not exceeding about 60°C, not exceeding about 55°C in other embodiments, not exceeding about 50°C in other embodiments, not exceeding about 40°C in some embodiments, and not exceeding about 30°C in yet other embodiments, especially at room temperature. Chemical fusion is effective for further reducing sheet resistance, and methods for achieving good fusion at room temperature are described. For the purposes of this article, room temperature can be considered to be about 16°C to about 28°C, but in some embodiments, it may be appropriate to consider the range of room temperature to be about 18°C to about 26°C, about 20°C to about 25°C, or other appropriate sub-ranges within the broad range provided. One of ordinary skill in the art will recognize that additional temperature ranges within the above explicit ranges are contemplated and are within the scope of the present disclosure. Drying can be promoted by gentle blowing with or without low-temperature heating of the air.
[0034] Since the initial attempts to use silver nanowires to form conductive coatings, efforts have been made to reduce the sheet resistance caused by the junction resistance between the nanowires. As shown by applicant's initial fusion studies, simple deposition of nanowire dispersions generally produces extremely high sheet resistance values, such as in the megaOhm / sq. range. See, for example, the '207 patent cited below. Various efforts have been made in this effort, such as applying pressure and using various energy sources. A corresponding problem is the processability of the nanowire ink in forming a consistent, high quality coating. Applicants have made an important leap in this effort through the invention of chemical fusion, which can be effective even if the unfused structure has extremely high sheet resistance.
[0035] As an aid to the fusion process, the applicant introduced processing aids, especially adhesives, to provide commercially processable and reproducible coating properties. In order to utilize these processing aids consistent with achieving fusion, the applicant found that adhesive selection is important. Hydrophilic adhesives are used, with particular success in the case of polysaccharide adhesives. Cellulose-based adhesives are conveniently used polysaccharides due to their extensive commercial use in many applications, including similar applications. Although not explicitly stated, the applicant's early research in the '968 patent cited below found that there was a considerable improvement in sheet resistance using polysaccharide adhesives without applying pressure or any further processing steps. Although not yet fully understood, appropriate polymers can reduce the junction resistance to approximately the extent when extremely high pressure is applied, while chemical fusion still provides significant further reduction due to the joining of silver nanowires when forming an integrated structure. Although not wishing to be limited by theory, this observation strongly suggests that some interactions between polysaccharide adhesives and metal nanowires allow the nanowires to be fairly close, so that the nanowires can be electrically associated with each other, and if the correct chemical reaction and processing are used, good conductivity can be achieved in the network of nanowires and polysaccharide adhesives. While not wishing to be bound by theory, this evidence also suggests some driving force and beneficial assembly between the polymer and the nanowires at the nanoscale that tends to increase silver-silver contacts while also providing significant surface association of the silver nanowires with the cellulose.
[0036] However, this early research still involved modest application of heat. Thus, the results in this paper show that there are superior results without applying any heat or applying very low amounts of heat, regardless of whether fusion occurs, but fusion produces further improvements. Furthermore, for even more mysterious reasons, some metal salts appear to inhibit full room temperature conductivity from establishing if fusion is not induced.
[0037] The results presented herein show that in comparable ink systems using the same nanowires, binder, and solvent, fusing with silver fluoride significantly favors fusing relative to silver acetate and possibly other silver salts. Silver fluoride was used as one of several fluxes tested in the '746 patent and provided comparable results to silver nitrate in the processing described in that patent. The results herein are in contrast to the silver acetate flux. As shown in the results in the examples below, attempts to fuse with silver acetate without any heating did not provide the desired results. With the switch to using silver fluoride salts, low sheet resistance values were observed herein while providing the desired optical properties. Evidence indicates that fusing occurs at room temperature with silver fluoride salts.
[0038] For room temperature fusion, the choice of metal source is important. In particular, silver fluoride (AgF) appears to be an appropriate silver salt. The metal ion source should be soluble. AgF was used in the early fusion studies described in the '968 patent, and various metal ion sources seemed to be roughly equivalent under the original process conditions. Further tests involving silver acetate as a flux showed that heating was required to induce the fusion process. In the current effort, AgF was tested, and the surprising results found that fusion occurred at room temperature using AgF, even though additional tests again failed to achieve fusion using AgOAc. Preliminary results using AgNO3 and AgBF4 indicate that low temperature fusion does not occur using these salts. This is confirmed in the results presented in the following examples.
[0039] Although applicants do not wish to be bound by theory, the results indicate that even if it is believed that the anion is a spectator in the relevant reaction, the anion identity may change the free energy of the reaction, and / or may affect various energy barriers associated with diffusion and / or reduction. In any case, these results strongly suggest that these systems are ready to have controlled fusion in the case of near equilibrium, so relatively moderate changes in free energy have observable effects. Other silver halides are insoluble in the relevant solvents, and soluble silver salts generally have anions that appear more similar to acetate anions.
[0040] Although applicants have achieved good sheet resistance using room temperature processing with or without fusing, fusing can effectively reduce sheet resistance without significantly affecting optical properties. In addition, in embodiments where the conductive layer is folded or stretched, it is believed that fusing significantly stabilizes the conductive coating. Therefore, for many applications, fusing is highly desirable.
[0041] For commercial inks, uniform coating on many substrates involves reducing the surface tension of ink. In principle, various surfactants can be used, and fluorosurfactants have been welcomed due to various practical reasons. Alcohol can serve as both a solvent and a wetting agent to form a good coating at higher concentrations. In the case of room temperature processing, it has been shown that high alcohol inks are effective in forming high conductivity coatings in the presence or absence of fusion. Alcohol can be selected to have a sufficiently low boiling point to evaporate relatively effectively at room temperature. The selection of alcohol may be related to the amount of alcohol used. Although depending on the placement position of a specific branched structure and hydroxyl groups, boiling points tend to increase with the increase of molecular weight, so higher alcohols with more carbon atoms tend to have higher boiling points, and correspondingly have lower vapor pressures at room temperature. In general, the alcohol of interest can be a C1 to C10 (based on the total number of carbon atoms in the molecule) alcohol with a concentration of 20 volume % to 100 volume % (based on solvent liquid).
[0042] In summary, the applicant's development efforts have provided high quality transparent conductive layers with excellent optical quality comparable to indium tin oxide in a material that is bendable and formable so that it can be stretched and repeatedly folded with durability for electrical conduction. On the other hand, higher levels of electrical conduction can be achieved at the expense of some transparency. It is even desirable to produce opaque thin conductive coatings using the room temperature processing described herein. These coatings can be formed on materials that can be temperature sensitive substrates and can be flexible. For embodiments that do not target good optical properties, lower quality silver nanowires can be used, which can allow for a larger proportion of non-nanowire nanoparticles, such as shapes blended with the nanowires.
[0043] Transparent materials are generally considered in the art to have an average transmittance of at least 70% for visible light, and this view is adopted herein. After room temperature processing, thin transparent conductive coatings can achieve a sheet resistance of approximately less than about 3 ohms / square. On the other end of the transmittance scale, room temperature processing can also achieve highly transparent conductive coatings with low haze and low L*, reflective scattering, and low sheet resistance. Therefore, heating is not required to achieve the excellent transparent conductive coatings previously achieved by applicants.
[0044] Chemical sintering has been discussed in the case of non-transparent structures. Using roughly spherical silver nanoparticles, room temperature sintering has been achieved in the case of a pre-coat or subsequent deposition of a cationic chlorinated polymer (polydiallyldimethylammonium chloride, poly-DADMAC). See the published U.S. patent application 2012 / 0168684 (hereinafter referred to as the '684 application) entitled "Process for Sintering Nanoparticles at Low Temperatures" by Magdassi et al., which is incorporated herein by reference. Poly-DADMAC is a polyelectrolyte that is not a desired component in many cases. In some embodiments, the '684 application describes the inclusion of a sintering salt, NaCl, in the nanoparticle dispersion, but for these systems, it is necessary to heat the deposited material to achieve sintering.
[0045] The '684 application claims a wide range of fluxes, although many of these fluxes clearly induce chemical fusion or effective agglomeration. Although the '684 application mentions carboxymethyl cellulose, it does not teach the appropriate use of a polysaccharide binder, and therefore it specifically does not exemplify good conductivity without chemical sintering based on halide ions and chlorides. It is believed that the current study, in which fusion of silver nanowires is used to form a fused metal nanostructured network at room temperature, is the first to form a thin conductive coating with a sheet resistance of less than 1000 ohms / square using any form of metal nanoparticles on an inert surface using a single ink deposition with or without fusion at room temperature.
[0046] Silver can provide excellent electrical conductivity. In order to form a non-transparent conductive coating, the characteristics of metal nanoparticles may become less important, but the processing methods herein are generally based on nanowire processing. When good transmittance and low scattering are important goals, silver nanowires can be manufactured to have higher purity to eliminate silver nanoparticles and other non-wire profiles that contribute the least to conductivity and cause light scattering. Similarly, in the process of manufacturing high-quality silver nanowires for high-quality transparent conductive coatings, a large amount of silver waste is generated, which has completely suitable silver materials except that the silver nanoparticles have low quality in terms of nanowire characteristics and have many spherical nanoparticles, thicker nanowires, short nanorods, nanoplates and / or nanoparticles of strange shapes. For forming a non-transparent thin conductive coating, high-quality nanowires are not required, so that the cost of generation can be significantly reduced. At higher silver loadings, any nanoparticles and other non-wire profiles can make greater contributions to electrical conduction by forming conductive paths with higher density.
[0047] It has been found that the fused metal nanostructured networks have improved properties in terms of high electrical conductivity and have desirable optical properties in terms of transparency and low haze. The fusion of adjacent metal nanowires can be performed based on a chemical process under commercially suitable processing conditions.
[0048] In particular, a significant advance in achieving conductive coatings based on metal nanowires is the discovery of a well-controlled process for forming a fused metal nanostructured network, in which adjacent segments of metal nanowires are fused into an integrated structure without the presence of distinct nanowires in the conductive network. In particular, it was initially discovered that halide ions can drive the fusion of metal nanowires to form fused metal nanostructures. Fluxes containing halide anions were introduced in various ways to successfully achieve fusion with a correspondingly significant drop in resistance. It should be noted that halide ions in this processing scenario should not be confused with halide ions used in nanowire synthesis reactions. In particular, fusion of metal nanowires using halide anions has been achieved using vapors and / or solutions of acidic halides and solutions of halide salts. Fusion of metal nanowires using halide sources is further described in U.S. Pat. No. 10,029,916 to Virkar et al., entitled “Metal Nanowire Networks and Transparent Conductive Material,” and U.S. Pat. No. 9,920,207 to Virkar et al., entitled “Metal Nanostructured Networks and Transparent Conductive Material” (the '207 patent), both of which are incorporated herein by reference.
[0049] Extensions of the process for forming fused metal nanowire networks are based on reduction / oxidation (redox) reactions, which can be provided to produce fused nanowires without destroying the optical properties of the resulting coating. The metal used for deposition at the junction can be effectively added as a dissolved metal salt, or can be dissolved from the metal nanowires themselves. The effective use of redox chemistry in fusing metal nanowires into nanostructured networks is further described in U.S. Patent No. 10,020,807 (the '807 patent), entitled "Fused Metal Nanostructured Networks, Fusing Solutions with Reducing Agents and Methods for Forming Metal Networks" by Virkar et al., which is incorporated herein by reference. The '807 patent also describes a single solution method for forming a fused metal nanostructured network. A single solution method for forming a fused metal nanostructured layer is further described in U.S. Patent 9,183,968 B1, entitled “Metal Nanowire Inks for the Formation of Transparent Conductive Films with Fused Networks” to Li et al. (hereinafter referred to as the '968 patent), which is incorporated herein by reference, and a single solution or ink process is used in the following examples to form a fused metal nanostructured network.
[0050] A single ink formulation provides a desired metal load to be deposited on the substrate surface as a coating, and simultaneously provides constituents in the ink that induce a fusion process when the ink is dried under appropriate conditions. These inks can be conveniently referred to as fused metal nanowire inks, where it is understood that fusion generally does not occur until drying. In some embodiments, the ink typically comprises an aqueous solvent, which may further comprise an alcohol and / or other organic solvent. The ink may also comprise a dissolved metal salt as a metal source for the fusion process. Without wishing to be limited by theory, it is believed that components of the ink (e.g., hydroxyl or other organic constituents) reduce metal ions from the solution to drive the fusion process. Previous experience with fusion processes in these systems has shown that metals are preferentially deposited at the junctions between adjacent metal nanowires. A polymer binder may be provided to stabilize the coating and affect the ink properties. Polysaccharides provide hydroxyl functional groups that can act to reduce silver ions. The specific formulation of the ink may be adjusted to select ink properties suitable for a specific deposition method and have specific coating properties on the substrate surface. As further described below, drying conditions may be selected to effectively carry out the fusion process.
[0051] For the room temperature fusion process, about blowing air over the deposited coating at room temperature, the process conditions can be optionally adjusted. If necessary, slight heating can be used in some embodiments. The airflow with or without heating can accelerate the solvent removal and the corresponding silver ion concentration to provide a reasonable fusion rate. As long as the ion mobility is maintained and the silver salt with sufficient reactivity is utilized, the solvent evaporation and drying (even at low temperatures) can produce fusion and excellent conductivity. Since hydrophilic adhesives are generally used, the water associated with the adhesive may be dried relatively slowly. The results presented in the embodiments have a sheet resistance value within a selectable value range, and in some embodiments have a sheet resistance value of about 35 ohms / square, and in another embodiment have a sheet resistance value of about 3 ohms / square, and relative to the sheet resistance value achieved, a good transmittance value is obtained.
[0052] In the case of lower temperature processing, the transparent conductive inks described herein even provide process advantages over non-transparent alternatives. Referring to Table 1 below, "typical" products refer to silver nanoparticle pastes or inks that have been commercially available for some time, examples of which are Toyobo 520H-19 or 520H-41, which cure at 130°C to 150°C for 30 minutes. Low temperature 1 products refer to the next generation of nanoparticle-based products that can be processed at slightly lower temperatures. Examples of commercially available low temperature silver pastes include those from DuPont TMPE828 ("ULTRA-LOW TEMPERATURE CURESILVER CONDUCTOR"), which can be processed at 60°C to 100°C.
[0053] Table 1
[0054]
[0055] The ability to form room temperature conductive coatings is both a desired processing improvement and the beginning of enabling processing of substrates that are susceptible to heat.
[0056] Silver Nanowire Ink and Deposition
[0057] In the case of silver nanowire inks, the desired processing of transparent conductive coatings tends to favor balance (balance close to equilibrium) and finesse rather than brute force, and it continues to apply to the desired processing methods described herein. These results are now extended to silver nanowire inks at room temperature, but the processing is even more gentle while achieving good conductivity. Therefore, the ink involves the appropriate selection of the appropriate amount of components. First, there are silver nanowires, and these silver nanowires are discussed in detail below, and if the optical properties are not too important or unimportant, the silver nanowires can be mixed with other nanoparticles. For transparent conductive coatings with good optical properties, high quality silver nanowires are discussed below. The solvent is typically aqueous and can have a small or large amount of alcohol. Surfactants (such as fluorosurfactants) may or may not be used, and the suitability of the surfactant may depend on the alcohol content of the solvent. Since fluorosurfactants may cause environmental problems, embodiments that avoid fluorosurfactants may be desirable from this perspective.
[0058] As a binder, polysaccharides are desirable, and in some embodiments, in the case of room temperature processing, other polymer binders should be avoided or extremely limited. As a flux, silver fluoride is desirable. In some embodiments, other components that adversely interact with silver ions to interfere with the fusion are limited or completely avoided. A person of ordinary skill in the art can empirically test a small amount of processing additives based on the teachings herein to check whether it is compatible with the formation of the conductive structure.
[0059] Silver nanowires and other nanoparticles can be selected as appropriate for the target application, and these can range from very thin and uniform nanowires of high quality to thicker nanowires and mixtures of nanoparticles and other nanoparticles. Transparent film applications typically utilize relatively pure silver nanowires. Applicants sell very high quality silver nanowires, such as those used in the examples below, which can be used to obtain excellent optical quality.
[0060] Minimally transparent, semi-transparent or opaque conductive layers can be formed from lower purity metal nanowire dispersions. Examples of conductive films that form transparent or semi-transparent coatings, but of lower optical quality, are presented below, formed from scrap of synthetic high purity silver nanowires, where the scrap contains a range of nanowire morphologies, nanoparticles, and various other nanoparticle shapes. This work points to the possibility of supplementing nanowires with other shapes of nanoparticles for non-transparent applications.
[0061] Silver provides excellent electrical conductivity. ® Ink sells silver nanowire inks for forming fused metal nanostructured networks. Other sources of silver nanowires are commercially available, and the basic fusion technology is described in detail in the '207 patent and the '807 patent referenced below. Fifth Generation (GEN5) ActiveGrid ® The vast majority (>98%) of the silver nanowires in the product have a diameter of less than <25 nm, and the seventh generation (GEN7) ActiveGrid ®The vast majority (>98%) of the silver nanowires in the nanowires have a silver nanowire diameter of <22 nm. The synthesis of thin silver nanowires is described in U.S. Pat. No. 10,714,230 B2, entitled "Thin and Uniform Silver Nanowires, Methods of Synthesis and Transparent Conductive Films Formed from the Nanowires" by Hu et al., which is incorporated herein by reference. High-quality silver nanowire products with small and uniform diameters and high purity are desirable for some applications of displays, but for applications with lower optical requirements, lower-grade silver nanowires may be sufficient. In this article, nanowires are considered to have an average diameter of less than 100 nm and less than 50 nm in some embodiments, and an average aspect ratio of at least about 10 nm and at least about 25 nm in other embodiments. Other commercial silver nanowires are commercially available. One of ordinary skill in the art will recognize that additional silver nanowire size ranges within the above-specified ranges are contemplated and are within the scope of the present disclosure.
[0062] The solvent is aqueous. The solvent may include alcohol, which may improve the rheology of the ink. If alcohol is used, the selection of alcohol is usually not critical, but alcohol should generally have a low boiling point to allow good drying at room temperature. From this perspective, alcohol is generally a monohydroxy fatty alcohol having no more than 10 carbon atoms, wherein methanol, ethanol, propanol, isopropanol, mixtures thereof, etc. are convenient. Many alcohols form low-boiling azeotropes with water, which, if present in an appropriate amount, are conducive to their evaporation. Therefore, the selection of alcohol may be affected by the amount of alcohol. In some embodiments, the solvent includes 0.1 volume percent (volume %), about 0.5 volume % to about 100 volume % in other embodiments and about 1 volume % to about 80 volume % in other embodiments. If necessary, the solvent may be conceptually divided into a high alcohol solvent having an alcohol greater than 51 volume % and a low alcohol solvent having an alcohol less than 50 volume %. Those of ordinary skill in the art will recognize that additional alcohol concentration ranges within the above-mentioned clear range are envisioned and are within the scope of the present disclosure. The solvent may also contain no more than about 5% by volume of other components such as polar solvents, for example, methyl ethyl ketone, glycol ethers (such as ethylene glycol methyl ether and propylene glycol methyl ether), methyl isobutyl ketone, toluene, hexane, ethyl acetate, butyl acetate, ethyl lactate, PGMEA (2-methoxy-1-methylethyl acetate), dimethyl carbonate, or mixtures thereof. Although the solvent should be selected based on the ability to form a good metal nanowire dispersion, the solvent should also be compatible with other selected additives such that the additives are soluble in the solvent.
[0063] For transparent applications, the ink required to achieve an effective single ink that solidifies into a fused nanostructured metal network contains the required amount of metal nanowires to achieve an appropriate metal loading in the resulting coating. The ink is stable in an appropriate solution before the ink is deposited and dried. The ink may contain a reasonable amount of a polymer binder that helps to form a stable conductive coating for further processing. In order to obtain good fusion results using an ink system, it has been found that hydrophilic polymers are effective as binders, particularly polymers such as cellulose, chitosan, xanthan gum or other polysaccharide-based polymers. As mentioned above, polysaccharides have shown significant properties in the case of binders for silver nanowires. Metal ions can be supplied as soluble metal salts as a metal source for the fusion process, and AgF is suitable for room temperature processing.
[0064] A single ink formulation provides for depositing the desired metal load as a coating on the substrate surface, and simultaneously provides constituents in the ink that induce a fusion process when the ink is dried under appropriate conditions. These inks can be conveniently referred to as fused metal nanowire inks, where it is understood that fusion generally does not occur until some drying occurs. As described above, the ink typically comprises an aqueous solvent, and the ink may also comprise a dissolved metal salt as a source of metal for the fusion process. Without wishing to be limited by theory, it is believed that components of the ink (e.g., hydroxyl moieties or other organic functional groups) reduce metal ions from the solution to drive the fusion process. Previous experience with fusion processes in these systems indicates that metals are preferentially deposited at the junctions between adjacent metal nanowires. A polymer binder may be provided to stabilize the film and affect the ink properties. The specific formulation of the ink may be adjusted to select ink properties suitable for a specific deposition method and to have specific coating properties on the substrate surface. As further described below, drying conditions may be selected to effectively carry out the fusion process.
[0065] The metal nanowire ink may contain about 0.01 wt % to about 3 wt % metal nanowires (nanoparticles), about 0.02 wt % to about 1.5 wt % metal nanowires (nanoparticles) in other embodiments, and about 0.04 wt % to about 1.0 wt % metal nanowires (nanoparticles) in other embodiments. Although for highly transparent embodiments, the nanoparticles remain low, for embodiments with lower optical requirements, the ink may contain significant amounts of other nanoparticle profiles. In some embodiments, the nanoparticles contain at least about 20 wt % nanowires, about 25 wt % to about 95 wt % metal nanowires in other embodiments, and about 30 wt % to about 80 wt % metal nanowires in other embodiments. Other nanoparticle profiles may vary and may be mixed, such as nanoparticles, nanocubes, nanoplates, etc. For embodiments of particular interest, the nanowires are silver nanowires, and the source of metal ions is a dissolved silver salt. The ink may contain silver ions at a concentration of about 0.01 mg / mL to about 2.0 mg / mL, in further embodiments about 0.02 mg / mL to about 1.75 mg / mL, and in other embodiments about 0.025 mg / mL to about 1.5 mg / mL. One of ordinary skill in the art will recognize that additional metal nanowire concentration ranges and metal ion concentration ranges within the explicit ranges above are contemplated and are within the scope of the present disclosure. The concentration of the metal nanowires affects the metal loading on the substrate surface as well as the physical properties of the ink.
[0066] Metal nanowires typically contain silver. Applicants have formed transparent conductive films with good optical properties using silver nanowires coated with precious metals. See U.S. Pat. No. 9,530,534 to Hu et al., entitled "Transparent Conductive Film," which is incorporated herein by reference. In general, other metal nanowires would be expected to have similar properties. Gold nanowires, platinum nanowires, palladium nanowires, copper nanowires, and other metal nanowires would be expected to exhibit similar performance.
[0067] With regard to ink formulations, polymer binders and solvents are generally selected in unison so that the polymer binder is soluble or dispersible in the solvent. In suitable embodiments, metal nanowire inks generally contain about 0.02% by weight to about 10% by weight of binder, about 0.05% by weight to about 8% by weight of binder in other embodiments, and about 0.1% by weight to about 5% by weight of polymer binder in other embodiments. Suitable binder concentrations may depend on the binder molecular weight. In some embodiments, the polysaccharide may have an average molecular weight of less than 10,000 g / mol. The weight ratio of the polymer binder relative to the metal nanowire / nanoparticle may also be important. The weight ratio of the polymer binder to the silver nanowire or nanoparticle may be at least about 0.05, at least about 0.1 in some embodiments, about 0.2 to about 3 in other embodiments, and about 0.3 to about 2 in other embodiments, as well as ranges with different combinations of these lower and upper endpoints. One of ordinary skill in the art will recognize that additional ranges within these explicit ranges are contemplated and are within the scope of the present disclosure. Desired binders include, for example, polysaccharides such as cellulose-based polymers, chitosan-based polymers, and the like. Suitable cellulosic binders include, for example, ether celluloses such as methyl cellulose, ethyl cellulose, ethyl methyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, hydroxyethyl methyl cellulose, hydroxypropyl methyl cellulose, carboxymethyl cellulose, mixtures thereof, and the like.
[0068] In some embodiments, nanowire inks may optionally include a rheology modifier or a combination thereof. In particular, the ink may include a wetting agent or surfactant to reduce surface tension, and the wetting agent may be used to improve coating properties. A wide range of surfactants such as nonionic surfactants, cationic surfactants, anionic surfactants, zwitterionic surfactants, and Gemini surfactants are commercially available. Fluorosurfactants can provide desired ink properties, but may be undesirable for some applications and final formulations. The purpose of fluorosurfactants is to act as wetting agents to provide lower surface tension, good wetting, and film formation on substrates. Wetting agents are generally soluble in the solvent used. In some embodiments, nanowire inks may include about 0.001% by weight to about 1% by weight of wetting agent, about 0.002% by weight to about 0.75% by weight of wetting agent in other embodiments, and about 0.003% by weight to about 0.6% by weight of wetting agent in other embodiments. Those of ordinary skill in the art will recognize that additional binder concentration ranges and wetting agent concentration ranges within the above-mentioned clear ranges are envisioned and are within the scope of the present disclosure. As mentioned above, higher alcohol concentrations in the solvent can provide effective wetting and processing. In some embodiments, in the case of high alcohol concentrations, it is found that the presence of a separate surfactant can inhibit room temperature processing, but in other low alcohol solvents, it is found that a separate surfactant works well. In general, other processing aids may or may not be used in various inks, such as thickeners, antioxidants, etc., and some of these processing aids may inhibit room temperature processing, while other processing aids may be good. Based on the teachings herein, those of ordinary skill in the art can easily test this. However, in general, other additives will not exceed about 5% by weight of the solids considered as non-volatile components.
[0069] Silver nanowires for commercial use are typically deposited by slit coating, and this can be done in roll-to-roll form. Both coating and fusing can be conveniently performed in this form. Applicants have outlined this processing for extremely thin polymer sheets with double-sided conductive coatings, as described in the published U.S. patent application 2020 / 0245457 entitled "Thin Flexible Structures With Surfaces With Transparent Conductive Films and Processes for Forming the Structures" by Chen et al., which is incorporated herein by reference. For uneven surfaces, dip coating, spraying, etc. can be used. In general, the same nanowire ink formulation for slit coating can be used for these alternative coating processes, but specific embodiments may suggest modifications. The conductive layer can be patterned using laser patterning or photolithography. Other similar coating processes can be used. Nanowire morphology complicates the printing of nanowire inks. Although rough printing of metal nanowire inks is conceivable, to the applicant's knowledge, printing of metal nanowire inks with good resolution for commercial production has not yet been achieved. There is a description of metal nanowire printing in U.S. Patent 8,454,859 to Lowenthal et al., entitled "Metallic Nanofiber Ink, Substantially Transparent Conductor, and Fabrication Method," which is incorporated herein by reference.
[0070] The amount of silver deposited affects the optical properties and sheet resistance. For highly transparent applications, the silver loading is usually selected to produce the desired conductivity, and the nanowire quality is important for the improvement of optical properties. The loading level of nanowires on the substrate is usually expressed as milligrams of nanowires per square meter of substrate and can be calculated based on the deposition. For transparent applications, the nanowire network can have about 1 mg / m 2 About 500 mg / m 2 In other embodiments, about 0.5 mg / m 2 About 200 mg / m 2 and in other embodiments about 1 mg / m 2 About 150 mg / m 2One of ordinary skill in the art will recognize that additional thickness and loading ranges within the explicit ranges above are contemplated and are within the scope of the present disclosure. If the sparse metal conductive layer is patterned, the discussion of thickness and loading applies only to areas where the metal is excluded or significantly reduced by the patterning process. For non-transparent applications, the metal loading is not particularly limited, but depending on the nanoparticle characteristics, there will be a range of semi-transparent metal loadings and then opaque films with even higher metal loadings. Multiple coatings can be performed to increase the loading and reduce the sheet resistance. The metal loading is effectively determined by the concentration of nanowires or other silver particles in the ink and the wet coating thickness.
[0071] For processing at room temperature, processing after the ink is applied can be minimized. For consistency and slightly faster drying, unheated air can be gently delivered to remove moisture. Whether or not air blowing is used, sufficient drying can be achieved within a few minutes to achieve fusion or achieve desired conductivity without the need for flux. These times are short compared to traditional coating processing times, so no effort has been made to push the times to even shorter amounts, but if necessary, the times can be optimized. An air knife or the like can also be used to dry the solvent to provide a final conductive film. It does not appear that air blowing is required to provide the desired results, but for commercial production, even if it is not strictly required, this can be an ideal choice to help ensure consistent product quality.
[0072] Although suitable systems do not require heat, some heat may also be applied. If some alternative solvents or some additives may affect processing, it is conceivable that some gentle heating may be advantageous in some embodiments. For example, the air blown in may be slightly heated, such as heated to the above-mentioned temperature, or the coated substrate may be placed in an oven with a sufficiently low temperature, etc. However, in general, in order to save costs and reduce environmental footprint and make processing available for a wider range of applications, it is advantageous to process without adding heat. In commercial coatings, it may be useful to use low temperature settings in infrared (IR), convection or other heating systems to carry out drying.
[0073] Conductive structure
[0074] Conductive structure can be designed to be suitable for specific application.Due to the large scope of the conductive coating formed by room temperature processing as described herein, the scope of coating properties can accordingly cover a wide range for different applications.Therefore, the property of the full range can be considered, and the coating can be grouped to help pay attention to the scope of potential target applications.For the reasonable grouping considered separately, it is selected as highly transparent (conductive layer transmittance is at least about 90%), transparent (conductive layer transmittance is about 70% to about 90%), semi-transparent (conductive layer transmittance is 0 to about 70%) and opaque (zero transmittance).These groupings are essentially arbitrary and fuzzy at the border, but according to potential application, these groupings seem to be reasonably divided and paid attention to.It should also be noted that the above-mentioned transparency relates to the visible light part of the electromagnetic spectrum, but this can extend to other parts of the spectrum, such as infrared.
[0075] As described above, transmittance varies with metal loading and nanowire mass (i.e., additional particles). In order to have transmittance through the conductor (rather than around the conductor), the metal coating should be sparse. The shape of the nanowires is suitable for forming a conductive path with large gaps for light to pass through, which the applicant refers to as a sparse metal layer. Although there is some scattering and absorption due to the plasmonic response or metal nanostructure, the nanowires are not resolved by visible light because the diameter of the nanowires is much lower than the wavelength of visible light, making the coating appear to be a uniform material under visible light. Metal nanowires are used to form transparent conductive layers because of their structure. Nanoparticles of other shapes cannot usually be formed into transparent conductive coatings because they cannot form conductive paths and holes of appropriate sizes for light to pass through the conductive structure.
[0076] As optical quality and high transmittance become less important, blends of nanoparticles become applicable. Thus, nanowires are not necessarily highly purified from other particle profiles. Nanoparticles and other odd silver particle shapes contribute disproportionately to scattering and reflection relative to their contribution to conductivity, but as optical properties become less important, the taboo on the presence of non-nanowire shapes also becomes less important. Thus, low transmittance and translucent conductive films can be formed at a lower cost than high quality nanowire coatings. Once the conductive coating becomes opaque, the coating may no longer be sparse, and the nanoparticle shape becomes less important, although the nanowires still contribute disproportionately to conductivity for their weight.
[0077] The loading and proportion of silver nanowires as a metal component therefore affects the properties of the processed coating. For sparse metal coatings with nanowires as the main metal component, the average thickness is somewhat imprecise due to the presence of gaps in the structure, but a rough thickness can be described if necessary, although the metal loading and nanowire diameter essentially describe the sparse coating. At the other extreme, for opaque structures, the processed coating can be closer to a uniform densified material. In principle, for opaque structures, the thickness is not limited.
[0078] Reference Figure 1 , representative conductive film 100 comprises substrate 102, optional primer 104, metal conductive layer 106, overcoat 108, adhesive layer 110 and protective surface layer 112, but not all embodiments include all layers. Although polymer sheet is an ideal substrate for many applications, for other substrates, film 100 can be equivalently regarded as a conductive structure, so "film" as used in this article can be equivalently regarded as any reasonable structure. For transparent embodiments, metal conductive layer 106 will be sparse, substrate 102 will be transparent, and adhesive layer will be optically transparent, and other layers can be made similarly appropriately transparent. Usually, adhesive layer 110 and protective surface layer 112 will be added after completing the important processing described herein, to improve the stability of one or more conductive layers. Transparent conductive film usually comprises sparse metal conductive layer and at least one layer on each side of the sparse metal conductive layer.
[0079] For transparent embodiments, the total thickness of the transparent conductive film can generally have an average thickness of 5 microns to about 2 millimeters (mm), about 10 microns to about 1 millimeter in other embodiments and about 12 microns to about 0.5 millimeter in other embodiments. It will be appreciated by those of ordinary skill in the art that other thickness ranges within the above-mentioned clear and explicit ranges are envisioned and are within the scope of the present disclosure. In some embodiments, the length and width of the produced film can be selected to be suitable for a specific application so that the film can be directly introduced to be further processed into a product. In additional or alternative embodiments, the width of the film can be selected for a specific application, and the length of the film can be long, wherein the desired film can be cut into a desired length for use. For example, the film can be in the form of a long sheet or roll. Similarly, in some embodiments, the film can be on a roll or in another large standard form, and the components of the film can be cut according to the desired length and width of use.
[0080] For potential application range, substrate composition can be selected from a wide range of possibilities, especially for opaque embodiments. Examples are provided on cardboard and fresh leaves, so even if some porosity can be tolerated, obviously extreme substrates may not be suitable. As mentioned above, for these more extensive applications, film can be regarded as a structure without significant meaning for the term of film. Therefore, glass and transparent ceramics together with polymers can be suitable for transparent embodiments, and ceramics, various organic and composite materials together with polymers can be substrates suitable for opaque embodiments. In general, due to the presence of melting, decomposition, unwanted reaction or other adverse transformation and influence (glass transition, softening, diffusion, color loss, modulus change), various polymer substrates and biological substrates require low processing temperatures. Therefore, the ability to produce conductive layers at ambient temperatures can make a large number of new applications and commercial products possible.
[0081] Substrate 102 can generally have any reasonable size. For many commercial applications, roll-to-roll processing can be a convenient form of processing. Typically, for roll-to-roll embodiments, substrates can have an average thickness of about 1 micron to about 1.5 millimeters, about 5 microns to about 1 millimeter in other embodiments and about 10 microns to about 500 microns in other embodiments. In particular, for foldable structures, especially double-sided foldable structures, substrate thickness can be no more than about 27 microns and about 5 microns to about 25 microns in other embodiments. Those of ordinary skill in the art will recognize that additional substrate thickness ranges within the above-mentioned clear range are envisioned and are within the scope of the present disclosure. Suitable optically transparent polymers with excellent transparency, low haze and good protection capabilities can be used for substrates.
[0082] Suitable polymers for transparent substrates include, for example, polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polyacrylates, poly(methyl methacrylate), polyolefins, polyvinyl chloride, fluoropolymers, polyamides, polyimides, polysulfones, polysiloxanes, polyetheretherketones, polyethersulfones, polynorbornene, polyesters, polystyrenes, polyurethanes, polyvinyl alcohols, polyvinyl acetates, acrylonitrile-butadiene-styrene copolymers, cycloolefin polymers, cycloolefin copolymers, polycarbonates, copolymers thereof, or blends thereof, etc. Suitable commercial polycarbonate substrates include, for example: MAKROFOL SR243 1-1 CG, commercially available from Bayer Material Science; TAP® plastics, commercially available from TAP Plastics; and LEXAN TM8010CDE, commercially available from SABIC Innovative Plastics. Optical quality PET substrates are available from, for example, DuPont-Teijin and Toray Films (Lumirror TM ). Polyimide substrates are available from Kolon, and polysulfone substrates are available from Solvay. Cyclic polyolefins (COP) are available from Zeon Corporation. The reduction in process temperature described herein allows the use of an even wider range of polymers and other substrates. For non-transparent substrates, most materials that can be reasonably coated can be used. The protective surface layer 112 can independently have a thickness and composition that covers the same thickness range and composition range as the substrates described above in this section.
[0083] If surface coating issues dominate, a primer layer can be applied. Thus, a thin polymer layer can provide a suitable surface for applying a conductive layer, although direct application of a conductive layer has been achieved on a range of materials. In addition, for many embodiments, an overcoat polymer may be desirable as a protective coating. The primer and / or overcoat polymers may independently include the polymer species described above for the substrate and may be applied by solution coating and optional subsequent crosslinking (such as by ultraviolet (UV) light exposure). The overcoat and primer polymers may be applied using the same techniques as nanowire inks. In particular, for less transparent or opaque embodiments, the thickness of these layers may not be important, but for transparent embodiments and some other embodiments, the overcoat may have an average thickness of about 5 nanometers to about 2 microns, about 7 nanometers to about 1 micron in other embodiments, and about 8 nanometers to about 250 nanometers in other embodiments. In some embodiments, the overcoat may include a crosslinked polyacrylate, a copolymer thereof, or a blend thereof.
[0084] The overcoat and / or undercoat may include a stabilizing compound that may help prolong good electrical conduction when exposed to environmental attack. Previous studies have found that vanadium (+5) compounds can effectively provide desired stability. See Yang et al., entitled "Stabilized Sparse Metal Conductive Films and Solutions for Delivery of Stabilizing Compounds" published U.S. Patent Application 2018 / 0105704 (hereinafter referred to as '704 Application), which is incorporated herein by reference. Others have found that iron (+2) and other metal salts can be effective stabilizers, see Allemand, entitled "Light Stability of Nanowire-Based Transparent Conductors", published U.S. Patent Application 2015 / 0270024A1, which is incorporated herein by reference. In addition, it has been found that cobalt (+2) ions coordinated with ligands provide stability within the fused metal nanostructured network layer. The performance of these stable compositions, alone or in combination, can be enhanced by incorporating precious metal ions, especially silver ions, within the coating (overcoat and / or undercoat) to further enhance stability, presumably due to further fusion of the structure with migration of the metal ions. During actual use of the structure in a product, the benefits of the precious metal ions in the coating can be utilized similar to pentavalent vanadium, but alternatively or additionally, it may be beneficial to have precious metal ions in the coating during post-deposition heat / humidity processing prior to assembly into a final product.
[0085] Suitable vanadium +5 compounds include compounds with vanadium as a cation and compounds with vanadium as part of a polyatomic anion, such as metavanadate (VO3 - ) or orthovanadate (VO4 -3). The corresponding salt compounds having a pentavalent vanadium anion in the oxometalate include, for example, ammonium metavanadate (NH4VO3), potassium metavanadate (KVO3), tetrabutylammonium vanadate (NBu4VO3), sodium metavanadate (NaVO3), sodium orthovanadate (Na3VO4), other metal salts, etc., or mixtures thereof. Suitable pentavalent vanadium cation compounds include, for example, vanadium oxytrialkoxide (VO(OR)3, R is an alkyl group, such as n-propyl, isopropyl, ethyl, n-butyl, etc., or a combination thereof), vanadium trihalide (VOX3, wherein X is Cl, F, Br, or a combination thereof), vanadium complexes such as VO2Z1Z2, wherein Z1 and Z2 are independently ligands, such as those further described below for Co+2 complexes, or combinations thereof. In the coating, there may be, for example, about 0.01% to about 9% by weight, about 0.02% to about 8% by weight in other embodiments, and about 0.05% to about 7.5% by weight of pentavalent vanadium in other embodiments. In the coating solution, the solution typically contains some solvent and solids that primarily contain a curable polymer. Typically, the corresponding coating solution may have a pentavalent vanadium compound at a concentration of about 0.0001% to about 1% by weight. One of ordinary skill in the art will recognize that additional concentration ranges within the above-defined ranges are contemplated and are within the scope of the present disclosure. In additional or alternative embodiments, iron (+2) or other metal ions may be included in addition to pentavalent vanadium ions, or may be included as an alternative to pentavalent vanadium ions.
[0086] In addition, noble metal ions, particularly silver ions, can also be included in the solution for forming the coating. As used herein, noble metal ions refer to ions of silver, gold, platinum, indium, osmium, ruthenium and rhodium. Noble metal ions can be added in the form of suitable salts (such as nitrates, sulfates, perchlorates, tetrafluoroborate, hexafluorophosphate, hexafluoroantimonate and halides, etc.). Suitable metal salts for providing metal ions include, for example, chloroauric acid and palladium chloride. For silver salts, if alcohol or other non-aqueous organic solvents are utilized to deposit the coating polymer, suitable silver salts and complexes for obtaining sufficient solubility include, for example, silver tetrafluoroborate (AgBF4), silver hexafluorophosphate (AgPF6), silver perchlorate (AgClO4), silver hexafluoroantimonate (AgSbF6), silver trifluoroacetate (AgCF3COO), silver heptafluorobutyrate (AgC4F7O2), silver methanesulfonate (AgCH3SO3), silver toluenesulfonate (AgCH3C6H4SO3), or mixtures thereof. In the coating, there may be, for example, about 0.01 wt % to about 20 wt %, about 0.05 wt % to about 15 wt % in further embodiments, about 0.1 wt % to about 12 wt % in other embodiments, about 0.2 wt % to about 9 wt % in some embodiments, and about 0.25 wt % to about 7.5 wt % of the noble metal ion in other embodiments. In the coating solution, the solution typically comprises some solvent and solids that primarily comprise a curable polymer. Those of ordinary skill in the art will recognize that additional concentration ranges within the above-defined ranges are contemplated and are within the scope of the present disclosure.
[0087] For direct use in transparent conductive layers, especially for transparent conductive layers with fused metal nanostructured networks, cobalt with a valence of +2 has been found to be effective for stabilization and does not interfere with the fusion process. Suitable cobalt compounds include, for example, Co(NO3)2 with various coordination ligands, such as nitrite (NO2 -), diethylamine, ethylenediamine (en), nitrilotriacetic acid (nitrilotriacetic acid), iminobis(methylenephosphonic acid), aminotri(methylenephosphonic acid), ethylenediaminetetraacetic acid (EDTA), 1,3-propylenediaminetetraacetic acid (1,3-PDTA), triethylenetetramine, tri(2-aminoethyl)amine, 1,10-phenanthroline, 1,10-phenanthroline-5,6-dione, 2,2'-bipyridine, 2,2'-bipyridine-4,4'-dicarboxylic acid, dimethylglyoxime, salicylaldehyde oxime, diethylenetriaminepentaacetic acid, 1,2-cyclohexanediaminotetraacetic acid, iminodiacetic acid, methyliminodiacetic acid, N-(2-acetamido)iminoacetic acid, N-(2-carboxyethyl)iminodiacetic acid, N-(2-carboxymethyl)iminodipropionic acid, picolinic acid, dipyridinecarboxylic acid, histidine, and combinations thereof. Previously, it has been proposed in the '807 patent cited above that cobalt ions are used as a suitable ion source for fusing metals at nanowire junctions. As shown in the '704 application, Co+2 actually makes transparent conductive films unstable unless it is coordinated with ligands. For the use of cobalt+2 stabilizing compounds in layers with fused metal nanostructured networks, stabilizing compounds will be added together with silver salts or other cationic salts that are more easily reduced so that cobalt+2 cations remain in the material after the fusion process. On the other hand, it has been found that stoichiometric ligands of Co+2 interfere with the fusion process to form a fused nanostructured network. In layers with fused metal nanostructured networks, the concentration of cobalt+2 stabilizing compounds can be from about 0.1% by weight to about 10% by weight, from about 0.02% by weight to about 8% by weight in other embodiments, and from about 0.025% by weight to about 7.5% by weight in other embodiments. In order for the cobalt composition to be effective without interfering with the fusion process, the coordinating ligand may be present in an amount of about 0.1 to about 2.6 ligand binding equivalents per mole of cobalt, in other embodiments about 0.5 to about 2.5 ligand binding equivalents per mole of cobalt, and in other embodiments about 0.75 to about 2.4 ligand binding equivalents per mole of cobalt. By equivalent, the term is intended to mean that the multidentate ligand has a corresponding molar ratio of the above range divided by its coordination number. For inks used to deposit metal nanowires, the solution may contain a cobalt +2 compound at a concentration of about 0.0001 wt % to about 1 wt %, although further details of the nanowire ink are as follows. One of ordinary skill in the art will recognize that additional concentration ranges within the explicit ranges above are contemplated and are within the scope of the present disclosure.
[0088] Coating properties
[0089] Conductive coatings can be formed to transparent or non-transparent layers. In appropriate embodiments, transparent conductive layers (such as those with fused metal nanostructured networks) can provide low resistance while providing good optical properties. Therefore, the structure can be used as a transparent conductive electrode, etc. The transparent conductive electrode can be suitable for a series of applications, such as electrodes along the light receiving surface of a solar cell. For displays, particularly touch screens, the film can be patterned to provide a conductive pattern formed by the structure. The substrate with a patterned structure generally has good optical properties in the respective parts of the pattern. Non-transparent layers (such as translucent or opaque layers) are generally formed under higher metal loadings to impart lower sheet resistance. For these coatings, haze and other optical properties are generally not particularly concerned.
[0090] The resistance of a thin coating can be expressed as a sheet resistance, which is reported in units of ohms / square (Ω / □ or ohms / sq) to distinguish sheet resistance values from bulk resistance values according to parameters associated with the measurement process. The sheet resistance along the surface can generally be measured using a four-point probe measurement or other suitable method. In some embodiments, the fused metal nanowire network can have a sheet resistance of no more than about 1000 ohms / square, no more than about 500 ohms / square in some embodiments, no more than about 200 ohms / square in some embodiments, no more than about 100 ohms / square in other embodiments, no more than about 80 ohms / square in other embodiments, and no more than about 50 ohms / square in some embodiments. For transparent films with visible light transmittance as low as about 70%, sheet resistance values have been reached as low as about 3 ohms / square, and some optimizations may make it slightly lower. For non-transparent coatings, sheet resistance values below 1 ohm / square can be achieved, and translucent coatings can be formed roughly in the range between these values. Although not limited by theory, it is believed that arbitrarily low resistance can be achieved by simply increasing the silver loading and / or by thicker coatings. One of ordinary skill in the art will appreciate that this system can be well modeled using a parallel resistor model, where the resistance can be estimated by the thickness. For example, if the conductive coating thickness is increased by a factor of 2 from the thickness that achieves 1 ohm / square, then the thicker (2x) film should have a resistance of 0.5 ohms / square. One of ordinary skill in the art will recognize that additional sheet resistance ranges within the explicit ranges above are contemplated and are within the scope of the present disclosure.
[0091] Depending on the specific application, commercial specifications for sheet resistance used as a transparent conductive film in a device may not necessarily involve lower sheet resistance values, such as when additional costs may be involved, and current commercially relevant values may be, for example, 250 ohms / square, versus 150 ohms / square, versus 100 ohms / square, versus 50 ohms / square, versus 40 ohms / square, versus 30 ohms / square, versus 20 ohms / square or lower, as target values for touch screens of different qualities and / or sizes, and these values are each limited to a range between specific values as the endpoints of the range, such as 150 ohms / square to 20 ohms / square, etc. Therefore, lower cost coatings may be suitable for certain applications in exchange for moderately higher sheet resistance values. In general, the sheet resistance can be reduced by increasing the loading of the nanowires, but from other perspectives, the loading increase may be undesirable, and the metal loading is only one of many factors in achieving low sheet resistance values.
[0092] Transparent conductive layers are typically formed with other optical properties in mind. On the other hand, translucent and opaque conductive layers are typically formed without particular attention to optical properties, but some attention to optical properties can be utilized based on the teachings herein. The following discussion relates to the optical properties of transparent coatings.
[0093] For applications as transparent conductive films, it is desirable that the fused metal nanowire network or other sparse metal conductive layer maintain good optical transparency. In principle, optical transparency is negatively correlated with loading, where higher loading leads to reduced transparency, but processing of the network can also significantly affect transparency. In addition, polymer binders and other additives can be selected to maintain good optical transparency. Optical transparency can be evaluated relative to the transmitted light through the substrate. For example, the transparency of the conductive film described herein can be measured by using a UV-visible spectrophotometer and measuring the total transmission through the conductive film and the supporting substrate. Transmittance is the ratio of the transmitted light intensity (I) to the incident light intensity (I o ) ratio. The transmittance through the coating (T 涂层 ) can be calculated by dividing the measured total transmittance (T) by the transmittance through the supporting substrate (T sub ) to estimate. (T = I / I o And T / T sub = (I / I o ) / (I sub / I o ) = I / I sub = T 涂层). Therefore, the reported total transmission can be corrected to remove the transmission through the substrate to obtain the transmission of the coating alone. Although it is generally desired to have good optical transparency over the entire visible spectrum, for convenience, the optical transmission at a wavelength of 550 nm can be reported. Alternatively or additionally, the transmission can be reported as the total transmittance of light with a wavelength of 400 nm to 700 nm, and such results are reported in the following examples. Generally, for fused metal nanowire films, the measurement of 550 nm transmittance and the total transmittance from 400 nm to 700 nm (or simply referred to as "total transmittance" for convenience) is not qualitatively different. In some embodiments, the coating formed by the fused network has a total transmittance (TT%) of at least 70%, in embodiments at least about 80%, in further embodiments at least about 85%, in further embodiments at least about 90%, in other embodiments at least about 94%, in further embodiments at least about 95%, and in some embodiments about 96% to about 99.5%. The transparency of films on transparent polymer substrates can be evaluated using the standard ASTM D1003 ("Standard Test Method for Haze and Luminous Transmittance of Transparent Plastics"), which is incorporated herein by reference. The TT% through the entire structure includes the reduction in transmittance due to the substrate and overcoat, and can shift the lower end point of the above transmittance range by 1% to 10%, and in some embodiments, by 2.5% to 5%. One of ordinary skill in the art will recognize that additional transmittance ranges within the above explicit ranges are contemplated and are within the scope of the present disclosure. When the measured optical properties of the coatings in the following examples for the substrates are adjusted, the coatings have excellent transmittance and haze values, which are achieved together with the observed low sheet resistance.
[0094] The fused metal network can also have low haze and high visible light transmittance, while having a desired low sheet resistance. The haze can be measured using a haze meter based on the above-mentioned ASTM D1003, and the haze contribution of the substrate can be removed to obtain the haze value of the transparent conductive film. In some embodiments, the transparent coating can have a haze value of no more than about 1.2%, no more than about 1.1% in some other embodiments, no more than about 1.0% in other embodiments, and as low as 0.1% in other embodiments. As described in the embodiments, using appropriately selected silver nanowires, extremely low haze values and sheet resistance values have been achieved simultaneously. The load can be adjusted to balance the sheet resistance value and the haze value, wherein extremely low haze values may be present while still having a good sheet resistance value. Specifically, a haze value of no more than 0.8% and a haze value of about 0.4% to about 0.7% in other embodiments can be achieved, and a sheet resistance value of at least about 45 ohms / square. In addition, haze values of 0.7% to about 1.2% and in some embodiments, haze values of about 0.75% to about 1.05% can be achieved, while sheet resistance values are from about 30 ohms / square to about 45 ohms / square. All of these coatings maintain good optical clarity. One of ordinary skill in the art will recognize that additional haze ranges within the above explicit ranges are contemplated and are within the scope of the present disclosure.
[0095] Example
[0096] General Materials and Methods
[0097] As shown in Table 2, inks S1 to S7 were prepared based on ActiveGrid® inks from applicant C3Nano. ActiveGrid® inks include fifth generation ActiveGrid® inks with an average diameter of silver nanowires < 25 nm, seventh generation ActiveGrid® inks with an average diameter of silver nanowires of about 18 nm, and eighth generation ActiveGrid® inks with an average diameter of silver nanowires of 13-15 nm. The inks include a hydroxyalkyl alkyl cellulose binder. Some ink formulations include silver salts AgOAc or AgF, and as detailed below for each example, different levels of each silver salt are used. Seventh generation (1× G7 ) ink and the eighth generation (1× G8 The standard level of AgF in the 5th generation ink (1×) is about 50% higher than that of the fifth generation ink. Silver salts are used in the inks of these examples and are referred to as NanoGlue® AgOAc and NanoGlue® HF.
[0098] Table 2
[0099]
[0100] The inks were coated on various polymer substrates as shown in Table 3. The substrates included 50 μm PET (polyethylene terephthalate) with and without a hard coat, and COP (cyclic olefin polymer). The inks were applied using a slot coater set to different gap thicknesses of 1.5 mils (38.1 μm) or 4.0 mils (101.6 μm). For some samples, the inks were applied using a No. 14 wire wound rod to provide a gap thickness of 1.4 mils (35.6 μm).
[0101] Table 3
[0102]
[0103] Samples are subjected to various processing conditions, as described in detail below for each embodiment. Some wet coatings were initially dried about 30 to 60 seconds at about 1.5 to 3 inches above the film using an air gun (with about 25°C of air at room temperature), and some wet coatings were further heated at different times in a baking oven heated at different temperatures in the range of 35°C to 120°C and in the range of 0.5 minutes to 210 minutes. Some wet coatings were dried at room temperature without any heating. Some wet coatings were dried at room temperature using a fan to blow cold air at about 21°C above the sample.
[0104] The average sheet resistance was measured using a sheet resistance measuring device from SURAGUS GmbH. The average total transmission percentage (%TT) and the average haze percentage (%H) were measured using a haze meter. The average b* was measured using a colorimeter.
[0105] In general, the processing to form the transparent conductive film is substantially as described in Example 5 of the '968 patent cited above, wherein the silver nanowires are synthesized as described in U.S. Pat. No. 10,714,230 B2, entitled “Thin and Uniform Silver Nanowires, Methods of Synthesis and Transparent Conductive Films Formed From the Nanowires,” to Hu et al., which is incorporated herein by reference.
[0106] Example 1 - Processing with or without heating using different fluxes
[0107] This example shows the performance of silver nanowire films with different silver salts dried and / or processed under different conditions as shown below in Tables 4 and 5. Coatings were prepared on primed PET with a gap thickness of 1.5 mils.
[0108] Table 4
[0109]
[0110] Table 5
[0111]
[0112] As shown in Table 4, Sample 2, which was dried in an oven at 120°C for 2 minutes, exhibited the lowest sheet resistance of 37 ohms / square. Samples 3 to 5, which were dried in an oven at 50°C for 90 to 210 minutes, exhibited similar sheet resistances of 42 to 43 ohms / square, such that the sheet resistance did not decrease significantly after 90 minutes, at least until 210 minutes. Sample 6, which was dried in an oven at 50°C for 60 minutes, exhibited a sheet resistance of 45 ohms / square. Thus, for Samples 3 to 9, which were dried at 50°C, the sheet resistance decreased with increasing drying time, with the sheet resistance gradually approaching the lowest value obtained for Sample 2, which was dried at 120°C. Even after 210 minutes, the samples dried at 50°C were presumably not fused to the same extent as Sample 2, which was dried at 120°C. Samples 1 and 10, which were dried in an oven without heating, exhibited the highest sheet resistance compared to the samples dried using heat. Sample 1, which was dried with a heat gun and not placed in an oven, had a sheet resistance of 57 ohms / square, while Sample 10, which was not dried with a heat gun or placed in an oven, had a sheet resistance of 64 ohms / square.
[0113] As shown in Table 5, samples 9 to 11 were not dried in an oven and exhibited the lowest sheet resistance of 31 to 32 ohms / square. Sample 9 was dried using only a heat gun, and samples 10 and 11 were dried without heating. Samples 2 to 5, dried at 50°C for 0.5 to 2 minutes, exhibited similar sheet resistances of 33 to 35 ohms / square, where samples 2 and 3 were duplicate samples. Regardless of temperature or time, samples 6 to 8, dried at 35°C to 40°C for 1 to 2 minutes, exhibited approximately the same sheet resistance, and were similar to the sheet resistance obtained at 50°C. Sample 1, dried at 120°C in an oven using a heat gun, exhibited a sheet resistance of 35 ohms / square, which may be comparable to or higher than the sheet resistance exhibited by samples 2 and 3 dried at 50°C.
[0114] The data shown in Tables 4 and 5 illustrate the differences in sheet resistance obtained using AgF versus AgOAc as a flux. The sheet resistance of S2, fused using AgF, was roughly independent of processing conditions, which was not the case for S1, fused using AgOAc. The sheet resistance of S2 was roughly the same at least for times ranging from 1 minute to 2 minutes regardless of the temperature ranging from room temperature to 120°C, however, the data indicate that unheated processing provides more desirable results in terms of sheet resistance than drying at temperatures as low as 35°C. The processing conditions for the samples containing AgF provided more desirable results in terms of sheet resistance than drying under any of the conditions studied when using AgOAc.
[0115] Example 2 - Processing with AgOAc with or without heating
[0116] This example shows the performance of silver nanowire films using different levels of AgOAc in the ink. Coatings with S1 ink were prepared by coating on double-sided HC-PET at a gap thickness of 1.5 mils. The data shown in Table 6 are for samples dried using cold air from a fan and are plotted on Figure 3 The data shown in Table 7 are for samples dried at room temperature and then heated at 120°C for 2 minutes and are plotted on Figure 4 Table 8 shows the difference between the data shown in Table 6 and Table 7.
[0117] Table 6
[0118]
[0119] 1. Relative amount relative to a reference amount and its multiples or fractions. Use fifth generation ink.
[0120] Table 7
[0121]
[0122] Table 8
[0123]
[0124] The data in Table 6 (cold air) show that the sheet resistance increases until the 1× level of AgOAc, but then drops to a level comparable to 0× at 1.5×. The data in Table 7 (heating at 120°C) show that the sheet resistance decreases with increasing AgOAc. For AgOAc present at a 1.5× level in the ink, the resulting sheet resistance is different depending on whether the sample is processed using cold air or heating at 120°C. The differences in properties between the room temperature processed values in Table 6 and the heat treated samples in Table 7 are presented in Table 8. As shown in Table 8, the sheet resistance of the sample with 1.5× AgOAc and processed using cold air is 158 ohms / square lower than the sample processed using heating at 120°C. Table 8 also shows that the sheet resistance of the sample without AgOAc and processed using cold air is 40 ohms / square greater than the sample processed using heating at 120°C. The behavior in Table 6 is somewhat surprising because the sheet resistance increases significantly simply by adding silver acetate. One plausible explanation is that silver acetate, as a polar salt, interferes with the interaction of the cellulose binder with the silver nanowires, or changes the microstructure of the film when the film is formed. Applicants have previously observed that the current system involving cellulose is very effective in inducing good interactions between unfused silver nanowires compared to other organic binders, so if this favorable microstructure is destroyed, high sheet resistance values may be observed. Some cellulose has the potential to enhance the contact of silver nanowires when forming a conductive film. At least this is the case for aqueous and alcohol systems. On the other hand, changes in the solvent system may still lead to very different results.
[0125] For %H, the data in Table 6 show that the values from 0.25× to 1× are approximately the same, but %H may increase at the 1.5× level. Although the 1.5× Nanoglue® level is useful for further reducing sheet resistance, some degradation of optical properties is observed. The data in Table 7 show the same trend, with a greater increase in %H at the 1.5× level. For %TT, the data in Tables 6 and 7 show that the values remain constant regardless of the processing conditions. For b*, the data in Table 6 show that the values from 0.25× to 1.5× are approximately the same, with an increase of about 0.1% compared to the 0× sample. The data in Table 7 show that when heating is compared to cold air, there is less increase at 0.25× to 1×, however, b* doubles at the 1× to 1.5× levels.
[0126] Example 3 - Processing with HF with or without heating
[0127] This example shows the performance of silver nanowire inks with 1× levels of HF versus fifth generation inks when coated at different thicknesses and subjected to different processing conditions.
[0128] The ink S2 with 1× level of HF was coated on the COP at a gap thickness of 1.5 mils or 4.0 mils, and samples of each thickness were processed as shown in Table 9. Since the ink concentration is unchanged, a larger gap thickness produces a proportionally larger metal loading. The S2 ink with a higher level of Ag (labeled Ag-1X) but with the same 1× level of AgF was also prepared and coated at a thickness of 4.0 mils and processed using cold air. The results are shown in Table 9. The transmittance of the overall structure is reported in Table 9 as well as the transmittance of only the transparent conductive film (TCF) in parentheses.
[0129] Table 9
[0130]
[0131] For samples prepared from ink S2 with 1× level of HF, the data in Table 9 show that for any thickness, the surface resistance or %TT shows little or no change with different processing conditions. The sample coated at 4.0 mil thickness shows about 26 ohms / square lower sheet resistance and about 3% to 4% lower %TT compared to the sample coated at 1.5 mils. Evidence indicates approximately complete fusion at room temperature (cold fan).
[0132] Depending on the processing conditions, at a thickness of 1.5 mils, the value of %H increased by about 0.1%, and at a thickness of 4.0 mils, the value of %H increased by about 0.35%. At a thickness of 1.5 mils, both samples exhibited a %H of 0.8 to 0.9. At a thickness of 4.0 mils, the effect of processing conditions was more significant, with the sample processed with cold air exhibiting a %H of 2.35%, and the sample processed at 120°C for 2 minutes exhibiting a %H of 2.70%.
[0133] Example 4 - Processing of ink with smaller diameter silver nanowires using HF
[0134] This example shows the performance of a silver nanowire ink comprising silver nanowires having a smaller diameter than the silver nanowires contained in the S3 ink of Example 3. G7 Horizontal HF's seventh generation ActiveGrid TM The inks were coated at different thicknesses and subjected to different processing conditions, but the base amount (1×) was a slightly higher concentration for the thinner nanowires.
[0135] The ink S4 with 1× level of HF was coated on the COP at a gap thickness of 1.5 mils or 4.0 mils, and samples of each thickness were processed as shown in Table 10. The S4 ink with a higher level of Ag (labeled Ag-1X) and the same 1× level of AgF was also prepared and coated at a thickness of 4.0 mils and processed using cold air. The results are shown in Table 10. The transmittance of the overall structure is reported in Table 10, as well as the transmittance of only the transparent conductive film (TCF) in parentheses.
[0136] Table 10
[0137]
[0138] For samples prepared by ink S4 with HF at 1× level, the data in Table 10 show that for any thickness, the surface resistance or %TT shows little or no change as the processing conditions vary. Compared to samples coated with 1.5 mils, samples coated with a thickness of 4.0 mils show a sheet resistance of about 23 ohms / square lower and a %TT of about 3% to 4% lower. The data on sheet resistance and %TT are comparable to those obtained for S2 inks prepared using fifth generation inks, but the sheet resistance is slightly lower. Again, these results show that approximately complete fusion seems to occur without applying any heat (cold fan). These results show that a clear coating (> 70%TT) can be formed with a sheet resistance of 3 ohms / square.
[0139] Depending on the processing conditions, at a thickness of 1.5 mils, the value of %H increased by about 0.1%, and at a thickness of 4.0 mils, the value of %H increased by about 0.37%. At a thickness of 1.5 mils, both samples exhibited a %H of 0.6% to 0.8%. At a thickness of 4.0 mils, the effect of processing conditions was more significant, with the sample processed with cold air exhibiting a %H of 1.76%, and the sample processed at 120°C for 2 minutes exhibiting a %H of 2.13%.
[0140] Example 5 - Comparison of inks with silver nanowires of different diameters with HF
[0141] Table 11 shows the difference between the data shown in Table 9 and Table 10.
[0142] Table 11
[0143]
[0144] The data shown in Table 11 show that the S4 inks generally exhibited lower average sheet resistance compared to the S3 ink. The %TT for all coatings ranged from about 92% to about 85%, with the exception of the S4 ink prepared with Ag-1× which exhibited a %TT of about 79%. The %H for the S4 inks was generally lower compared to the S2 ink, with the exception of the S4 ink prepared with Ag-1× which exhibited an increase of about 1.3%.
[0145] Example 6 - Processing of ink with AgF using cold air
[0146] This example explores the performance of ink coatings on different polymer substrates when the ink is processed by using cold air drying for about 1 to 5 minutes. The inks are formulated with silver nanowires with different diameters and the coatings have different thicknesses. The variation of coatings and performance data are summarized in Table 12. The transmittance of the overall structure is reported in Table 12 as well as the transmittance of the transparent conductive film (TCF) alone in parentheses.
[0147] Table 12
[0148]
[0149] The data shown in Table 12 show that coatings prepared from S4 ink generally exhibit lower average sheet resistance than S2 ink. The %TT for all coatings ranged from about 89% to about 92%. The %H for S4 ink was generally smaller than that for S2 ink. Coatings prepared using a gap thickness of 4.0 mils exhibited lower sheet resistance than the corresponding 1.5 mil coatings, with thicker coatings having slightly lower %TT, and thicker coatings having slightly higher %H. Overall, there were little or no differences between primed PET, hard-coated PET, and COP.
[0150] Example 7 - Processing of inks with and without AgF using cold air
[0151] This example further explores the performance of ink coatings with and without AgF as a flux. The inks were formulated with silver nanowires of varying average diameters and coated on COP and PU, respectively. All samples were processed by using cold air drying. The changes in coating and performance data are summarized in Table 13. The transmittance of the overall structure and the transmittance of only the transparent conductive film (TCF) in brackets are reported in Table 13.
[0152] Table 13
[0153]
[0154] The data shown in Table 13 show that coatings prepared using flux in the ink generally exhibit lower average sheet resistance than corresponding coatings without flux. The sheet resistance differences of coatings prepared on PU were greater than those of COP. For example, the S7 ink and S4 ink coated on COP each exhibited a difference of -45 ohms / square, while the difference on PU was -94 ohms / square. All coatings exhibited a %TT of about 92%. Little or no change in %H was observed between inks with and without flux, and overall, coatings prepared on PU were greater than coatings prepared on COP.
[0155] Example 8 - Optical and Conductive Properties of Inks Processed at Ambient Conditions
[0156] This example further illustrates the optical properties and conductivity of ink coatings processed under ambient conditions.
[0157] Inks with various AgNW loadings were coated on COP at different (4.0 mil, 3.0 mil, and 1.5 mil) gap thicknesses to achieve various sheet resistances, and the samples were processed for about 1 minute at ambient conditions. Selected properties were evaluated and reported for the structures and only the transparent conductive film (TCF) in parentheses. A graph of the sheet resistance data is shown in Table 14. The transmittance of the bulk state is reported in Table 14, while the transmittance of the bulk state is reported in Table 14. Figure 5 and Figure 6 %TT and %H are shown in FIG.
[0158] Table 14
[0159]
[0160] 1. Dry for 1 minute at ambient conditions; on COP
[0161] 2. Valuation
[0162] The results show that for ink coatings dried under ambient conditions, excellent optical properties as well as desirable conductive properties can be obtained.
[0163] The ink containing fifth generation nanowires and AgF is formed as a coating or circuit on a variety of substrates including heat sensitive substrates and dried under ambient conditions. Substrates include medical grade polyurethane, medical bandages, leaves, Ziploc® bags, shrink wrap, Scotch TM Adhesive tape (coating on the adhesive layer of the tape), PET and packaging paperboard. 7A to 7H As shown, the resistance was measured by direct contact measurement. Although rough resistance measurements were attempted, no attempt was made to obtain accurate measurements for many of these substrates, and the nature of the substrates resulted in uncertainty.
[0164] Example 9 - Differences in the formulations of high alcohol ink and AgF ink
[0165] This example shows the performance of inks prepared using alcohol as the primary solvent compared to water, and the performance differences associated with the presence of fluorosurfactants in the ink. In general, cellulose used as a binder is soluble in EtOH-H2O mixtures.
[0166] Fifth generation ActiveGrid in 80% ethanol in water TM Inks Inks with high alcohol content were prepared. Inks were prepared in the presence and absence of nonionic fluorosurfactants as wetting agents and in the presence and absence of AgF as fluxing agents. The formulations are summarized in Table 15. S8 ink to S11 ink were coated on hard-coated PET (as shown in Table 2) with a gap thickness of 1.5 mils. The coatings were dried at room temperature with a fan blowing cold air at about 21°C over the samples. The results are shown in Table 16. The transmittance of the overall structure and the transmittance of only the transparent conductive film (TCF) in brackets are reported in Table 16.
[0167] Table 15
[0168]
[0169] 1. 0.05 wt% 3M Novec TM FC-4430
[0170] Table 16
[0171]
[0172] 1. Heat further at 120°C for 5 minutes
[0173] For S8 and S9, which do not contain a wetting agent, the sheet resistance drops by 38 ohms / square if flux is present, and little or no difference is observed in %TT, %H, and b*. For S10 and S11, which contain a wetting agent, the sheet resistance drops by 700 ohms / square if flux is present, and little or no difference is observed in %TT, %H, and b*. However, the sheet resistance of S10 and S11 is significantly greater than that of S8 and S9, for example, 84 ohms / square for S8 and 900 ohms / square for S10. %TT, %H, and b* are roughly the same for all coatings.
[0174] Example 10 - High alcohol ink, NaF added
[0175] This example shows the performance of inks prepared using alcohol as the primary solvent compared to water, and the differences in performance associated with the presence of alkaline fluoride salts in the ink.
[0176] Fifth generation ActiveGrid in 64%-70% ethanol in water TM Ink Preparation Inks with high alcohol content were prepared. Inks were prepared using AgOAc, AgF, NaF and equimolar combinations of AgOAc and NaF. The recipes are summarized in Table 17. S12 ink to S16 ink were coated on HC-PET with a gap thickness of 1.5 mils. As shown in Table 17, the coatings were processed differently. Some coatings were dried at room temperature, with a fan blowing cold air at about 21°C over the sample. After measuring the sheet resistance of the resulting film, the sample was further heated at 120°C for 2 minutes. The results are shown in Tables 17 to 19. The transmittance of the overall structure and the transmittance of only the transparent conductive film (TCF) in brackets are reported in Table 19.
[0177] Table 17
[0178]
[0179] Table 18
[0180]
[0181] Table 19
[0182]
[0183] The data from Tables 17 to 19 are plotted on Figure 8 and Fig. 9 middle. Figure 8 The relationship between the inverse of the sheet resistance and the haze of S12 to S16 processed under the above-mentioned conditions is shown. Fig. 9 A comparison of sheet resistance values obtained for coatings with the same flux or without flux is shown. For S12 to S16, if the coatings are heated after drying at room temperature, the sheet resistance drops by more than 10 ohms / square, except for S13 where the sheet resistance remains approximately the same. S13 also provides the lowest sheet resistance. For %TT and %H, small or no differences are observed, however, if heating is used, b* increases by about 0.3 to about 0.6. This example shows that fluoride anions alone do not drive room temperature fusion at the levels used. Therefore, the data indicate that the unique combination of silver cations and fluoride anions is important.
[0184] Example 11 - Properties of Byproduct Silver Nanoparticle Ink
[0185] This example shows the performance of an ink prepared from silver byproducts generated from the synthesis of silver nanowires.
[0186] A byproduct silver nanoparticle mixture is recovered from the centrifugation residue of a purification process used to produce fifth generation silver nanowires.
[0187] The three samples were characterized using titration and thermogravimetric analysis (745°C), and the results are summarized in Table 21.
[0188] Table 20
[0189]
[0190] 1. Titration
[0191] 2. Thermogravimetric analysis
[0192] Ink S17 was formulated using byproduct W1 at 4×Ag loading and 1×cellulose binder using AgF as flux. Ink S18 was formulated using the same ratios of all components except that the concentration of all solids was approximately 60% higher than in ink S17.
[0193] Table 21
[0194]
[0195] Ink S19 was formulated using byproduct W2 (W1 filtered through a 400 mesh filter) with 4x Ag loading and 1x cellulose binder using AgF as flux. Ink S20 was formulated identically to ink S19 except that no flux was added.
[0196] Table 22
[0197]
[0198] Using AgF as flux, the byproduct W3 (W1 was further concentrated by an agglomeration step) was used to formulate ink S21 with 4×Ag loading and 1×cellulose binder.
[0199] Table 23
[0200]
[0201] The above embodiments are intended to be illustrative and not restrictive. Additional embodiments are within the scope of the claims. In addition, although the present invention has been described with reference to specific embodiments, those skilled in the art will recognize that changes can be made in form and detail without departing from the spirit and scope of the present invention. Any incorporation of references as above is limited so that no subject matter that contradicts the explicit disclosure herein is incorporated. Insofar as a specific structure, composition and / or process is described herein with components, assemblies, ingredients or other parts, it should be understood that the disclosure herein covers the specific embodiments; embodiments comprising the specific components, assemblies, ingredients, other parts or combinations thereof; and embodiments that are substantially composed of such specific components, ingredients or other parts or combinations thereof and that may include other features that do not change the basic properties of the subject matter, as suggested in the discussion, unless otherwise specifically stated. The term "about" used herein refers to the expected uncertainty of the relevant value as will be understood by a person of ordinary skill in the art in a specific context.
Claims
1. A method for forming a conductive layer, the method comprising: depositing a metal nanowire ink onto an inert surface to form a coating, the ink comprising about 0.001 wt % to about 4 wt % of the metal nanowires and about 0.05 wt % to about 5 wt % of the polysaccharide; as well as The coating is dried at room temperature to form a conductive film having a sheet resistance of no more than about 1000 ohms / square. 2 . The method of claim 1 , wherein the metal nanowires comprise silver nanowires and the metal nanowire ink comprises a silver salt.
3. The method of claim 1, wherein the metal nanowire ink comprises 0.001 mg / mL to about 2.0 mg / mL of silver ions, and wherein a fused metal nanostructure network is formed after drying. The method of claim 2 , wherein the silver salt comprises AgF.
5. The method of claim 1, wherein the sheet resistance is less than about 100 ohms / square and the coating has a %TT of at least about 98.6%. The method of claim 1 , wherein the sheet resistance is less than about 100 ohms / square.
7. The method of claim 1 , wherein the inert surface is a surface of a polymer substrate and the substrate with the coating forms a conductive film exhibiting a total transmittance of at least about 90%, a haze of less than about 1.0%, and a b* of less than about 2.
0.
8. The method of claim 1, wherein the metal nanowire ink does not contain added metal salts.
9. The method of claim 8, wherein the inert surface is a surface of a polymer substrate and the substrate with the coating forms a conductive film that exhibits a total transmittance percentage of at least about 90%, a haze of less than about 1.0%, and a b* of less than about 1.
0.
10. An ink for forming a conductive layer, the ink comprising: about 0.001 wt % to about 4 wt % of metal nanowires and about 0.05 wt % to about 5 wt % of a hydroxyalkyl functionalized polymer binder, and about 20 vol % to about 100 vol % of a C1 to C 10 An aqueous solvent of an alcohol, and no more than about 0.001% by weight of a surfactant.
11. The ink of claim 10, wherein the hydroxyalkyl-functional polymer binder comprises cellulose.
12. The ink of claim 10, wherein the hydroxyalkyl-functional polymer binder comprises an alkyl cellulose, a hydroxyalkyl cellulose, or a mixture thereof.
13. The ink of claim 10, wherein the ink further comprises 0.001 mg / mL to about 2.0 mg / mL of a metal ion.
14. The ink of claim 10, wherein the metal nanowires comprise silver nanowires.
15. The ink of claim 14, wherein the ink further comprises a silver salt.
16. The ink of claim 15, wherein the silver salt comprises AgOAc or AgF.
17. The ink of claim 16, wherein the silver ions from the silver salt are present in an amount of 0.001 mg / mL to about 2.0 mg / mL.
18. The ink of claim 10, wherein the metal nanowires have an average diameter of 25 nm or less.
19. The ink of claim 10, wherein the metal nanowires have an average diameter of 20 nm or less.
20. The ink of claim 10, wherein the metal nanowires have an average diameter of 15 nm or less.
21. The ink of claim 10, wherein the metal nanowires have a noble metal coating.
22. The ink according to claim 10, wherein the C1 to C 10 The alcohols include C1 to C5 alcohols.
23. The ink of claim 10, wherein the surfactant comprises a nonionic surfactant.
24. The ink of claim 10, wherein the surfactant comprises a fluorinated surfactant.
25. A method for forming a conductive coating having very low sheet resistance, the method comprising: applying a silver nanoparticle ink to a substrate surface to form a wet coating, the ink comprising an aqueous solvent, silver nanoparticles having no more than 85% by weight of silver nanowires having an average diameter of 50 nm or less and an aspect ratio of 10 or greater, and a cellulose binder; and The wet coating is dried at a temperature not exceeding 60° C. to form a dry coating having a sheet resistance not exceeding 25 ohms / square.
26. The method of claim 25, wherein the ink comprises a silver salt.
27. The method of claim 25, wherein the ink comprises 0.001 mg / mL to about 2.0 mg / mL of silver ions, and wherein a fused silver nanostructure network is formed upon drying.
28. The method of claim 26, wherein the silver salt comprises AgF.
29. The method of claim 25, wherein the sheet resistance is less than about 20 ohms / square and the coating has a %TT of at least about 50%.
30. The method of claim 25, wherein the ink is formed from a solution used to synthesize the silver nanowires.
31. The method of claim 25, wherein the inert surface is a surface of a polymer substrate.
32. The method of claim 25, wherein the ink contains no added metal salts.
33. The method of claim 25, wherein the ink comprises from about 30 wt% to about 80 wt% silver nanowires relative to total silver nanoparticles.
34. The method of claim 25, wherein the ink comprises a solvent having greater than 51% alcohol by volume and is free of fluorosurfactants.
35. A silver nanoparticle ink, comprising: an aqueous solvent, silver nanoparticles comprising no more than 85 wt% of silver nanowires having an average diameter of 50 nm or less and an aspect ratio of 10 or more, and a cellulose binder, wherein the weight ratio of cellulose to silver nanoparticles is from about 0.05 to about 3.
36. The ink of claim 35, wherein the ink comprises: about 0.001 wt % to about 4 wt % of silver nanowires and about 0.05 wt % to about 5 wt % of a hydroxyalkyl functionalized polymer binder, comprising about 20 vol % to about 100 vol % of a C1 to C 10 An aqueous solvent of an alcohol, and no more than about 0.001% by weight of a surfactant.
37. The ink of claim 35, wherein the cellulosic binder comprises a hydroxyalkyl functionalized polymer binder.
38. The ink of claim 35, wherein the cellulosic binder comprises a hydroxyalkyl functionalized polymer binder, an alkyl cellulose, a hydroxyalkyl cellulose, or a mixture thereof.
39. The ink of claim 35, wherein the ink further comprises 0.001 mg / mL to about 2.0 mg / mL of silver ions.
40. The ink of claim 35, wherein the ink further comprises a silver salt.
41. The ink of claim 40, wherein the silver salt comprises AgOAc or AgF.
42. The ink of claim 40, wherein the silver ions from the silver salt are present in an amount of about 0.001 mg / mL to about 2.0 mg / mL.
43. The ink of claim 35, wherein the silver nanoparticles are provided in the form of a solution for synthesizing silver nanowires.
44. The ink of claim 35, wherein the silver nanowires have a noble metal coating.
45. The ink according to claim 36, wherein the C1 to C 10 The alcohols include C1 to C5 alcohols.
46. The ink of claim 36, wherein the ink does not contain a fluorosurfactant.
47. The ink of claim 35, wherein the silver nanoparticles further comprise spherical nanoparticles, nanorods, nanoplates, nanocubes, oddly shaped nanoparticles, or mixtures thereof.
48. The ink of claim 35, wherein the silver nanoparticles further comprise silver nanowires having an average diameter greater than 50 nm.
49. The ink of claim 34, wherein the silver nanoparticles comprise from about 30 wt% to about 80 wt% silver nanowires, and the ink has from about 0.2 wt% to about 3 wt% silver nanoparticles.
Citation Information
Patent Citations
Fused metal nanostructured networks, fusing solutions with reducing agents and methods for forming metal networks
US10020807B2
Metal nanowire networks and transparent conductive material
US10029916B2
Thin and uniform silver nanowires, method of synthesis and transparent conductive films formed from the nanowires
US10714230B2
Process for sintering nanoparticles at low temperatures
US20120168684A1
Light stability of nanowire-based transparent conductors
US20150270024A1